Análise da contribuição do programa de inclusão social Crediamigo Crescer para os microempreendedores de baixa renda na cidade de Fortaleza no ano de 2012 - Freitas, Paulo Sérgio Sales (2013)
This study had objective to analyze Crediamigo Crescer in the city of Fortaleza in the year of 2012 and the impact of this microcredit program. For this the inquiry makes a comparison between two different groups, a control group and a treatment group, formed by the first customers recently captured by the BNB, with less than one year, so no big impact of the lending on the activity and the second group formed for customers with more than two years of experience with microcredit, where is already perceived the result of investment in working capital in the activity. The comparison will be made from statistical data provided by the BNB and the answer the applications in a sample of enterprisers in the city of Fortaleza. It was found that the profile of the enterprisers from Fortaleza is female, married or in stable relationships, aged between 18 and 50 years, who exerts commercial activity and has a low level of education, because the most of them have the high school level incomplete. It was concluded that the Crediamigo Crescer has significant impact on the lives of enterprisers, because it supplied them an improvement of life, as in improving the activity increased with products, and improvement of structure of work, where was verified behind the applications the improvement in the quality of life of the enterprisers, as in realization of the dream of the own home, the best educational facilities for dependents, providing access to private schools and colleges and the acquisition of durable products such as cars, motorcycles, televisions, refrigerators, stoves, and others.